1978
DOI: 10.1128/aem.35.6.1046-1051.1978
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular accumulation of a new amino acid, O-2-hydroxypropylhomoserine, from 1,2-propanediol by flavobacterium rigense

Abstract: During an investigation of microorganisms utilizing petrochemicals, a strain identified as Flavobacterium rigense was found to accumulate a new amino acid in a medium containing 1,2-propanediol as the sole carbon source. Cultural conditions for the accumulation of the product were investigated, and, as a result, the yield was increased to 2.8 mg/ml after a 5-day incubation in a medium containing 8% 1,2-propanediol. The pure amino acid was isolated, and its structure was investigated. Elemental analysis and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1979
1979
1981
1981

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Our previous paper (11) reported that a potent L-glutamine (L-Gln) producer, distinct from the so-called general group of L-glutamic acid-producing bacteria (6), was isolated from penicillinresistant mutants derived from Flavobacterium rigense FERM-P 3556, which was reported as a strain producing O-hydroxypropylhomoserine (10). The strain, designated 703, produced 10 mg of L-Gln per ml in a chemically defined medium.…”
mentioning
confidence: 99%
“…Our previous paper (11) reported that a potent L-glutamine (L-Gln) producer, distinct from the so-called general group of L-glutamic acid-producing bacteria (6), was isolated from penicillinresistant mutants derived from Flavobacterium rigense FERM-P 3556, which was reported as a strain producing O-hydroxypropylhomoserine (10). The strain, designated 703, produced 10 mg of L-Gln per ml in a chemically defined medium.…”
mentioning
confidence: 99%
“…Our previous paper described the isolation of Flavobacterium rigense FERM-P no. 3556, a strain that produces large amounts of a new amino acid, 0-2-hydroxypropylhomoserine, from 1,2-propanediol (17). This strain accumulated L-glutamic acid (L-Glu) and L-glutamine (L-Gln) in the culture broth when 1,2-propanediol was replaced by glucose as the sole carbon source.…”
mentioning
confidence: 99%